Assessing House Prices with Prudential and Valuation Measures - Andrle, Michal (IMF Working Papers; Working Paper ;, 2019)
In this paper we provide tools for assessing the house prices and housing valuation. We develop two approaches: (i) borrowing capacity approach, and (ii) intrinsic value approach. The borrowing capacity of households, together with their down payment, implies how much housing they can attain. In the intrinsic value approach, property value is viewed as a discounted present value of adjusted net rental income. Our approach does not involve a complex econometric model and only widely available data are used. The proposed indicators can guide households, financial markets and macroprudential authorities in their understanding of house prices development. To illustrate the concepts, we analyze the housing prices in the Czech Republic and assess the degree of market over-and undervaluation.